2021
DOI: 10.3390/membranes11040230
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Nanofiltration Process Using DSPM-DE Model for Purification of Amine Solution

Abstract: The formation of heat stable salts (HSS) during the natural gas sweetening process by amine solvent causes many problems such as corrosion, foaming, capacity reduction, and amine loss. A modeling study was carried out for the removal of HSS ions from amine solution using nanofiltration (NF) membrane process that ensures the reuse of amine solution for gas sweetening. This model studies the physics of the nanofiltration process by adjusting and investigating pore radius, the effects of membrane charge, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Various authors have investigated the transport of neutral and colloidal solutes, along with their respective rejection in membrane processes [71,82,83]. From a comparative analysis of various models developed to describe NF, it was concluded that the Nernst-Planck equation was the most suitable for predicting the mechanisms of transport and ionic selectivity in NF [84][85][86][87]. Subsequently, the Donnan Steric Partitioning Model (DSPM) was applied, based on the extended Nernst-Planck equation, modified by incorporating hindered transport factors for both diffusion and convection [71,88,89].…”
Section: Modeling Of Mass Transport In Nfmentioning
confidence: 99%
“…Various authors have investigated the transport of neutral and colloidal solutes, along with their respective rejection in membrane processes [71,82,83]. From a comparative analysis of various models developed to describe NF, it was concluded that the Nernst-Planck equation was the most suitable for predicting the mechanisms of transport and ionic selectivity in NF [84][85][86][87]. Subsequently, the Donnan Steric Partitioning Model (DSPM) was applied, based on the extended Nernst-Planck equation, modified by incorporating hindered transport factors for both diffusion and convection [71,88,89].…”
Section: Modeling Of Mass Transport In Nfmentioning
confidence: 99%
“…Table S2: Parameters used for case study 1 in Equations ( 1) and (5). Permeances (Equation ( 1)) of the artificial equimolar mixture of the dissolved salts MA and M 2 B are taken from Yaroshchuk and Bruening [14]. Table S3: Case Study 1-used parameters without optimization in modeling with constant pump pressure (8 bar) in Equations (S1), (S2), (S5), and (S6).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Nevertheless, there are models to describe aqueous nanofiltration, such as the Spiegler-Kedem transport model [10], Teorrell-Meyer-Sievers model [11] and the Donnan-steric-pore-dielectric exclusion model (DSPM-DE) [12]. The latter has been applied for different nanofiltration applications, such as the separation of NaCl /Na 2 SO 4 [13], the purification of amine solutions [14], and the prediction of rejection of various single salt solutions [15]. Wang and Lin [16] stated that the DSPM-DE model requires excessive experiments and lacks in prediction performance.…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating the dielectric effect into the DSPM, this model is referred to as the Donnan steric pore model with dielectric exclusion (DSPM–DE) model. More recently, this model has been used widely by various researchers [ 77 , 78 , 79 , 80 ]. One of the highlighted studies explored the effect of dielectric constant in NF membrane [ 81 ].…”
Section: Non-sieving Mechanismmentioning
confidence: 99%